A psicologia e o programa de saúde da família :novas possibilidades, velhos dogmas? - Silva, Fabiana Lima (2004)
The model of attention to health has been suffering alterations due to the difficulty faced to put into practice its universal, democratic and institutional layout. Since the movement of Sanitary Reform, which focused in the demands of a new health context and the process of work in the area of health, one seeks uninterruptedly, to find a way which leads to the execution of the principles of SUS. Despite having tried, the model of Sanitary Vigilance centered within the work of a multi-professional team has shown fragmentation and little adequacy to the necessity of health in the population. Whilst inserting himself in the field of health, the psychology professional has taken with him his clinic way of attending to individuals being one more in the team to act in a de-contextualised and little critical way. In virtue of this framework, the Ministry of Health invests in the Family Health Program as a new guide in the health system, restructuring the basic attention at a new logic of action. In this way, the municipality of Natal-RN implants, in the year 2002, the PSF in the Northern Sanitary District, a context in which professional teams are created where there is not an inclusion of a psychologist. Consequently, this professional is excluded of his work space in the previous Basic Unities of Health. This piece of work constitutes in the investigation of the implementation and instrumentalization of the Northern Sanitary District PSF of Natal-RN, having as its objective to analyze the implications of this execution for the structuring of the health network services and more specifically the alterations that this implementation could be making to the practice of the Psychology Professionals, emphasizing its advances, obstacles and limitations. To make this work feasible it was necessary to search for data and information from the implementation and execution of the PSF in the DSN, carrying interviews from a semi-structured guide, with 21 institutional actors (members of the team, coordinators and directors of the unities and psychologists)